An Elegant Biosensor Molecular Beacon Probe: Challenges and Recent Solutions. (13th December 2012) - Kolpashchikov, Dmitry M.
Abstract : Molecular beacon (MB) probes are fluorophore- and quencher-labeled short synthetic DNAs folded in a stem-loop shape. Since the first report by Tyagi and Kramer, it has become a widely accepted tool for nucleic acid analysis and triggered a cascade of related developments in the field of molecular sensing. The unprecedented success of MB probes stems from their ability to detect specific DNA or RNA sequences immediately after hybridization with no need to wash out the unbound probe (instantaneous format). Importantly, the hairpin structure of the probe is responsible for both the low fluorescent background and improved selectivity. Furthermore, the signal is generated in a reversible manner; thus, if the analyte is removed, the signal is reduced to the background. This paper highlights the advantages of MB probes and discusses the approaches that address the challenges in MB probe design. Variations of MB-based assays tackle the problem of stem invasion, improve SNP genotyping and signal-to-noise ratio, as well as address the challenges of detecting folded RNA and DNA.